Proyeksi Kebutuhan Energi Listrik dengan Metode Regresi Linear Berganda di UP3 Mojokerto Tahun 2022 sampai 2027 - Mirelle Ferent Hasnitha; RB. Moch. Gozali; Suprihadi Prasetyono (Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2023)
Demand for the availability of electrical energy in the future requires good planning and forecasting. Based on data from BPS (Badan Pusat Statik) East Java, the population and the number of electricity customers in East Java province has increased every year. So a forecasting can be done to find out the estimated demand for electrical energy needs in the future. In this study using multiple regression analysis method to project electricity demand in UP3 Mojokerto from 2022 to 2027. The results of the 2022 projection will be compared with the actual data in 2022 for data validation with the calculation of MAPE (Mean Absolute Percent Error). The resulting MAPE value is less than 10%, which means that this multiple linear regression method is a very good method used to project electrical energy demand at UP3 Mojokerto in 2022-2027. That way, the results of projected electrical energy demand with multiple linear regression methods in UP3 Mojokerto in 2022 amounted to 4,937,341 MWh, and in 2023 to 2027 the projected electrical energy demand increased successively by 5,323,722 MWh, 5,721,631 MWh, 6,131,543 MWh, 6,553,951 MWh, and 6,989,371 MWh. With an average growth from 2022 to 2027 of 6.30%.